The Adverse Effects of Estrogen and Selective Estrogen Receptor Modulators on Hemostasis and Thrombosis - Artero, Arturo; Tarín, Juan J.; Cano, Antonio (Seminars in Thrombosis and Hemostasis, 2012)
Agonists of the estrogen receptor include estrogens and selective estrogen receptor modulators (SERMs). Both types of compounds increase the risk for thrombosis in the arterial and the venous tree. The magnitude of the effect is influenced by potency, which depends on the type of compound and the dose. The particulars of the process change in each territory. Atherosclerosis, which creates local inflammatory conditions, may favor thrombogenesis in arteries. A direct effect of estrogen agonists is also well endorsed at both arteries, as suggested from data with high-estrogenic contraceptives, and veins. Dose reduction has been proved to be an effective strategy, but there is debate on whether additional benefit may be attained beyond a certain threshold. Hormone therapy and SERMs exhibit a lower potency estrogenic profile, but are mainly used by older women, who have a baseline increased thrombogenic risk. When used as sole agents, estrogens substantially reduce the increased risk (venous thrombosis) or may even be neutral (coronary disease). SERMs exhibit a neutral profile for coronary disease and possibly for stroke but not for venous thrombosis.
Keywords: contraceptive; estrogen; hormone therapy; SERM; thrombosis